Metabolomics combined with transcriptomics and physiology reveals the regulatory responses of soybean plants to drought stress - Wang, Liwei; He, Peijin; Hui, Mengmeng; Li, Hainan; Sun, Anni; Yin, Hong; Gao, Xining (Frontiers in Genetics, 2024)
Drought, a prevalent environmental stressor, has had significant consequences on soybean (Glycine max L.), notably impeding its growth and production. Therefore, it is crucial to gain insight into the regulatory responses of soybean plants exposed to drought stress during soybean flowering in the field. In this study, the cultivar ‘Liaodou 15’ was performed light drought (LD, 24.3% soil moisture content), moderate drought (MD, 20.6% soil moisture content) and severe drought (SD, 16.9% soil moisture content) treatments at flowering stages of soybean and then rehydrated (30% soil moisture content) until harvest. The yield-related indicators were measured and revealed that MD and SD treatments significantly reduced 6.3% and 10.8% of the 100-grain weight. Soybean plants subjected to three drought stresses showed that net photosynthetic rates were 20.8%, 51.5% and 71.8% lower in LD, MD and SD than that of CK. The WUE increased by 31.8%, 31.5% and 18.8% under three drought stress treatments compared to CK. In addition, proline content was 25.94%, 41.01% and 65.43% greater than that of CK under three drought stress treatments. The trend of the MDA content was consistent with that of the proline content. SOD activity was significantly increasing by 10.86%, 46.73% and 14.54% under three drought stress treatments. The activity of CAT in the SD treatment increased by 49.28%. All the indices recovered after rehydration. Furthermore, 54,78 and 51 different expressed metabolomics (DEMs) were identified in the LDCK/LD, MDCK/MD and SDCK/SD groups, respectively. There were 1,211, 1,265 and 1,288 different expressed genes (DEGs) were upregulated and 1,003, 1,819 and 1,747 DEGs were downregulated. Finally, combined transcriptomic and metabolomic analysis suggested that 437 DEGs and 24 DEMs of LDCK/LD group, 741 DEGs and 35 DEMs of MDCK/MD group, 633 DEGs and 23 DEMs of SDCK/SD group, were highly positively correlated in soybean plants under drought stress. Drought stress induced the expression of the PAO1, PAO4, PAO5 and P5CS genes to promote the accumulation of spermidine and proline. Our study elucidates the responses of drought-stressed soybean plants in the field and provides a genetic basis for the breeding of drought-tolerant soybean plants.